Epidemiology and Laboratory Diagnoses of Rubella in Hokkaido District during the Nationwide Outbreak in Japan, 2011–2013 - Miyoshi, Masahiro; Komagome, Rika; Ishida, Setsuko; Nagano, Hideki; Okano, Motohiko (Japanese Journal of Infectious Diseases, 2014)
We report the epidemiology and laboratory diagnostic results of rubella cases from 2011 to 2013 in Hokkaido district, Japan. A total of 150 cases were officially reported as rubella; 102 (68%) involved males and 48 (32%) involved females. The highest proportion of cases were notified in 40–49-year-old age group among males and the 20–29-years-old age group among females. Forty-six cases (25 males and 21 females) had not been vaccinated, and 17 had been vaccinated, whereas 87 had the unknown vaccination status. Eighty-three cases (55.3%) showed the 3 typical principal rubella symptoms (fever, rash, and lymphadenopathy). Seven, 11, 92, and 40 cases were identified in the northern, eastern, central, and southern areas of Hokkaido district, respectively. In the central and southern areas of Hokkaido district, endemic rubella transmissions were indicated by both the epidemiological survey and molecular analyses. However, these outbreaks terminated spontaneously and did not expand to other areas of Hokkaido district. Fortunately, no congenital rubella syndrome (CRS) cases were reported during this observation period. However, to control virus transmission, prevent CRS, and maintain the routine vaccination program, the immediate introduction of an immunization strategy is required for susceptible individuals, particularly young adults.